Personality Traits of Profoundly Hearing Impaired Adolescents with Cochlear Implants – A Comparison with Normal Hearing Peers - Boerrigter, Merle; Vermeulen, Anneke; Marres, Henri; Langereis, Margreet (Frontiers in Psychology, 2018)
The aim of this study was to compare the personality traits of adolescents with CI’s to a reference group (normal-hearing peers). In the past the personality development of hearing impaired adolescents was severely compromised. Improved speech perception with cochlear implant (CI) significantly increased their perspectives. In addition, differences between the reference group and CI users were investigated on personality traits according to level of speech perception skills (high/low) and level of language comprehension (adequate/poor). A cohort of 59 adolescents was assessed 10 years after CI implantation. Personality traits were measured using the standardized Dutch Personality Questionnaire, which consists of 5 scales: Inadequacy, Social Inadequacy, Recalcitrance, Perseverance and Dominance. Speech perception and language comprehension were tested with standardized tests. The distributions of personality scores, in the clinical or non clinical range, for the CI group were compared to the reference group using the Chi-Square test for Goodness of Fit. Adolescents with CI showed normal or favorable distributions on all personality scales except for the recalcitrance scale. There was a significant influence of speech perception and language comprehension on this scale. Consequently, adolescents with CI who demonstrated high speech perception and adequate language comprehension scores showed similar distribution patterns as the reference group on all personality scales. In conclusion; personality traits that reflect social relations, self-conscience and school- and task orientation in adolescents with CI are similar to those in normal-hearing peers. This holds, despite variations in speech perception ability and language comprehension levels, for the CI group. On the recalcitrance scale the adolescents with CI with low speech perception and poor language comprehension scores are more likely to score in the clinical deviant range and are at risk.